TNF-α Inhibitors and Other Biologic Agents for the Treatment of Immune Checkpoint Inhibitor-Induced Myocarditis - Xiaohang Liu; Wei Wu; Ligang Fang; Yingxian Liu; Wei Chen (Frontiers in Immunology, 2022)
With anti-PD-1 antibodies serving as a representative drug, immune checkpoint inhibitors (ICIs) have become the main drugs used to treat many advanced malignant tumors. However, immune-related adverse events (irAEs), which might involve multiple organ disorders, should not be ignored. ICI-induced myocarditis is an uncommon but life-threatening irAE. Glucocorticoids are the first choice of treatment for patients with ICI-induced myocarditis, but high proportions of steroid-refractory and steroid-resistant cases persist. According to present guidelines, tumor necrosis factor alpha (TNF-α) inhibitors are recommended for patients who fail to respond to steroid therapy and suffer from severe cardiac toxicity, although evidence-based studies are lacking. On the other hand, TNF-α inhibitors are contraindicated in patients with moderate-to-severe heart failure. This review summarizes real-world data from TNF-α inhibitors and other biologic agents for ICI-induced myocarditis to provide more evidence of the efficacy and safety of TNF-α inhibitors and other biologic agents.